HALLYU WAVE DAN PERUBAHAN SOSIAL: MEMBANGUN KOMUNITAS REMAJA DI INDONESIA SERTA DAMPAKNYA TERHADAP WARISAN BUDAYA LOKAL - Amelia Surya Wardhoyo, Claudya; Damayanti Putri, Syafida (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
The Hallyu Wave phenomenon has had a significant impact on social life in Indonesia, particularly among teenagers. This article examines how the Hallyu Wave shapes the identity and social solidarity of Indonesian teenagers, as well as its influence on the preservation and transformation of local culture. This research adopts a qualitative approach, utilizing media content analysis and observations on the influence of Korean culture through digital platforms. The results indicate that the Hallyu Wave is not merely entertainment, but also a tool for identity formation. However, this phenomenon has the potential to shift local cultural values. The findings emphasize the importance of maintaining a balance between appreciating foreign culture and preserving Indonesian culture to prevent the loss of local cultural heritage among the younger generation.